Effect of soaking on the germination and emergence of tagasastus (chamaecytisus proliferus L.Fil) (Agroindustria, Sociedad y Ambiente, 2026)
Tagasaste belongs to the Fabaceae family, species Chamaecytisus proliferus L. Fil, and is propagated by seed; however, it has very low germination and emergence rates due to the hardness of the seeds. The objective of this study was to investigate the effects of soaking in water and scarification with sulfuric acid on Tagasaste seeds in relation to germination and emergence. The trial was established at the La Neblina farm, located at 09° 46’38.54” N and 69° 35’24.76” W, at 1710 m above sea level. The seeds were exposed to different treatments: T1 = Soaking in normal water (48 hours), T2 = 98% H2SO4 for 15 min, T3 = 98% H2SO4 for 10 min, and T4 = Control (no scarification). The seeds were placed in Petri dishes to germinate. The experiment was established using a completely randomized design with 4 treatments and 4 replicates. After scarification, the seeds were sown in bags with sterilized substrate. Observations were made daily regarding the time of emergence and the total percentage of emergence. The results obtained using sulfuric acid yielded germination rates of 97.94% and 34.82%, respectively. Soaking in water and the control group only produced 3.35% and 1.94%, respectively. The emergence percentages of the seeds treated with sulfuric acid showed the highest values. The use of sulfuric acid proved beneficial for the germination and emergence processes; however, it is necessary to determine the optimal application times to avoid damage to the embryo.
Keywords: Soaking, scarification, seed, emergence, germination.